Investigation of hydrogen isotope retention mechanisms in beryllium: High resolution TPD measurements. (May 2019) - Eichler, Michael
Highlights: Hydrogen isotope retention mechanisms are investigated using temperature programmed desorption spectroscopy. High precision temperature programmed desorption spectra resolve low temperature desorption peak of implanted deuterium in beryllium for the first time. SEM images show cracked up blisters on beryllium surface after deuterium implantation. Desorption spectra of beryllium single and poly crystals with various fluences and different temperature ramps are compared and discussed. Abstract: The retention of ion-implanted deuterium in beryllium poly- and single crystals at room temperature is studied using high precision temperature programmed desorption spectroscopy (TPD). Slow temperature ramps of 0.01 K/s in combination with well-defined experimental conditions are used to resolve the low temperature desorption regime for the first time revealing three sharp desorption peaks. The comparison to results of a coupled reaction diffusion system (CRDS) model shows, that the corresponding release mechanisms cannot be described by thermally activated rate processes. SEM images of a polycrystalline beryllium sample after implantation of deuterium with 2 keV per D atom show the formation of blisters of roughly 1 µm in diameter. Additionally, cracks on top of the blisters are found as well as spots, on which blisters are peeled off. Both processes are discussed to play a role in the low temperature release regime of the retained deuterium. Investigation of TPD spectra performed on single crystalline beryllium shows a jagged pattern in the low temperature release regime, which can be connected to blisters bursting up, releasing big amounts of deuterium in short time scales.